UJI EFEKTIVITAS KOMBINASI PERASAN BUAH LABU AIR DAN JAHE MERAH SEBAGAI ANTIBAKTERI Salmonella typhi - Djohan, Herlinda; Triana, Linda; Nurhayati, Etiek (Jurnal Laboratorium Khatulistiwa, 2024)
Typhoid fever is an acute disease caused by the bacteria Salmonella typhi. This bacteria is usually found in contaminated water or food. Apart from that, this bacteria can also be transmitted from infected people. The treatment carried out is using modern drugs such as the antibiotic chloramphenicol. However, the use of modern medicine has several disadvantages such as side effects. On the other hand, the use of natural ingredients as natural medicine has been widely used. One of them is that water gourd is empirically used as a fever reducer. Water gourd contains secondary metabolites, namely saponins, steroids and phenols which have been proven to have antibacterial activity and are able to inhibit the growth of Salmonella typhi bacteria. Another natural ingredient that has antibacterial activity is red ginger. Red ginger contains active compounds that have antibacterial effects such as flavonoids, phenols, treponoids and essential oils. Antibacterial activity was obtained by measuring the diameter of the inhibition zone after administering 4 variations of the concentration of the juice sample. The positive control used amoxicillin 30 µg/disk and the negative control used distilled water. The research design used was a quasi-experimental method. The samples were water gourd and red ginger juice with varying concentrations of 40%, 60%, 80% and 100% and the average inhibition zone values were obtained, namely 8.875 mm, 9.875 mm, 11.25 mm and 14.25 mm. Based on the results of research and computerized data processing using the Kruskall Walis test, a value of p = 0.000 (p<0.05) was obtained, which means that there is an effect of the concentration of pumpkin juice and red ginger on the inhibitory power of Salmonella thypi bacteria.